2016
DOI: 10.1155/2016/3419479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeic Acid Phenethyl Ester on Vascular Damage Caused by Consumption of High Fructose Corn Syrup in Rats

Abstract: Fructose corn syrup is cheap sweetener and prolongs the shelf life of products, but fructose intake causes hyperinsulinemia, hypertriglyceridemia, and hypertension. All of them are referred to as metabolic syndrome and they are risk factors for cardiovascular diseases. Hence, the harmful effects of increased fructose intake on health and their prevention should take greater consideration. Caffeic Acid Phenethyl Ester (CAPE) has beneficial effects on metabolic syndrome and vascular function which is important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In another study using CAPE against the high-fructose corn syrup diet-induced vascular damage in rats, blood pressure values were significantly reduced after a two-week intraperitoneal injection with CA derivative. This study also noted that CAPE has the ability to correct the reduced levels of endothelial NO synthase levels caused by the high-fructose corn syrup diet [ 73 ].…”
Section: Ca Vs Hypertensionmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study using CAPE against the high-fructose corn syrup diet-induced vascular damage in rats, blood pressure values were significantly reduced after a two-week intraperitoneal injection with CA derivative. This study also noted that CAPE has the ability to correct the reduced levels of endothelial NO synthase levels caused by the high-fructose corn syrup diet [ 73 ].…”
Section: Ca Vs Hypertensionmentioning
confidence: 98%
“…CA was found able to reduce the levels of endoplasmic reticulum stress markers in the liver after a HFD obese induction [ 72 ]. Besides CA’s ability to revert dyslipidemia by reducing TG and TC, studies have shown that CA was able to revert hepatic steatosis in the long run [ 49 , 73 , 74 , 75 ]. In a recent in vivo study, a 12 week CA supplementation on HFD obese mice revealed that CA was able to reduce body weight and fat accumulation together with readings of improved lipid profile with an increased HDL [ 56 ].…”
Section: Ca Vs Dyslipidemiamentioning
confidence: 99%
“…Hydroxytyrosol was obtained in liquid form from Kale Natural Herbal Products Company in Turkey, and 4 ml/kg of this liquid that contained HT was administered orally to the rats in Groups II and IV each day for 6 weeks. The rats in Groups III and IV were given 30% corn syrup mixed into their drinking water for 6 weeks [24]. At the end of 6 weeks, IP Ketamine (75 mg/kg) and Xylazine (10 mg/kg) was given to the rats to anesthetize the animals prior to sacrifice.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…This beneficial effect was not observed in healthy controls, suggesting that orally administered CAPE may exert a higher impact in animals with a higher vascular tone, a hallmark of insulin resistance and insulin deficiency ( El-Bassossy et al, 2012 ). In high fructose consumer diabetic rats, subacute CAPE administrations (50 μmol/kg/day intraperitoneally for 2 weeks) ameliorate the rise in blood pressure that accompanies this metabolically mediated vascular damage, and was attributed to increased eNOS levels, even though an anti-inflammatory effect cannot be ruled out ( Gun et al, 2016 ). Furthermore, as CAPE is also able to reduce insulin resistance ( Hassan et al, 2014 ), it can be argued that this blood pressure-lowering effect might also be attributed to increased vasculature sensitivity to insulin’s vasorelaxant action.…”
Section: Biological Activities On the Cardiovascular Systemmentioning
confidence: 99%
“…Furthermore, it also inhibits leucocyte adhesion and vascular inflammation ( Förstermann and Sessa, 2012 ). Caffeic acid increases the endothelial production of NO in HUVECs by inducing the expression and increasing the activity of eNOS ( Wallerath et al, 2005 ; Gun et al, 2016 ) or by scavenging ROS, which prevents NO destruction ( Migliori et al, 2015 ). In vivo studies seem to support that CA and CAPE enhance eNOS expression ( Khanna et al, 2005 ; Long et al, 2009 ; Gun et al, 2016 ).…”
Section: Biological Activities On the Cardiovascular Systemmentioning
confidence: 99%